Moda de novela : os conteúdos de Salve Jorge divulgados em revistas femininas e as estrelas como padrões-modelo de estilo e beleza - Lopes, Jenara Miranda (2014)
This dissertation intends to verify the roles assumed by soap operas, and its stars, as motivators of the consumption of fashion items inspired by its characters wardrobe, and understand how they and women s fashion magazines together act as trendsetters. During the Salve Jorge Brazilian soap opera broadcasting, a monitoring of women s magazines and its posterior content analysis were conducted to determine the relationship established between these publications and soap operas, from the star images used in covers till the subjects of soap operas used as magazine contents. Through Edgar Morin s Star System theory, as well as Michel Maffesoli and Gilles Lipovetsky postmodern theories, it s noticed that the uses of star images, as well as the spectator s familiarity with the soap operas contents, act as consumption stimulus, both materially, from the indication of products consumed by celebrities, and culturally, through the consumption of the media themselves. This study could also establish the existence of a national Star System, generated and explored by Brazilian media.